Overview of antimicrobial therapy in intensive care units. Issue 1 (January 2011) - Textoris, Julien; Wiramus, Sandrine; Martin, Claude; Leone, Marc
In the management of a patient with severe sepsis, it is important to suspect the infection early, to collect samples immediately after diagnosis and to promptly initiate a broad-spectrum antibiotic treatment. The choice of this empirical antimicrobial therapy should be based on host characteristics, site of infection, local ecology and pharmacokinetics/pharmacodynamics of antibiotics. In severe infection, guidelines recommend the use of a combination of antibiotics. After results of cultures are obtained, treatment should be re-evaluated to either de-escalate or escalate the antibiotic prescription. This is associated with optimal costs, decreased incidence of superinfection and minimal development of antimicrobial resistance. All these steps should rely on written protocols, and the compliance to these protocols should be continuously monitored in order to detect violations and implement corrective procedures.